Pulmonary arterial hypertension in systemic sclerosis: Diagnosis and treatment according to the European Society of Cardiology and European Respiratory Society 2015 guidelines. Issue 1 (February 2019) - Giordano, Nicola; Corallo, Claudio; Chirico, Chiara; Brazzi, Angelica; Marinetti, Adriana; Fioravanti, Antonella; Valenti, Roberto; Nuti, Ranuccio; Pecetti, Gianluca
Scleroderma (systemic sclerosis) is an autoimmune connective tissue disease which presents endothelial dysfunction and fibroblast dysregulation, resulting in vascular and fibrotic disorders. Pulmonary hypertension is frequent in patients with systemic sclerosis: the natural evolution of the disease can induce the development of different forms of pulmonary hypertension, representing one of the main causes of death. Among the different forms of pulmonary hypertension in systemic sclerosis, pulmonary arterial hypertension is the most frequent one (rate of occurrence is estimated between 7% and 12%). This pulmonary vascular complication should be treated with a combination of drugs that is able to counteract endothelial dysfunction, antagonizing the endothelin-1 system and replacing prostaglandin I2 and nitric oxide activity. A correct diagnosis is mandatory, because it is possible only for pulmonary arterial hypertension to use specific drugs that are able to control the symptomatic condition and the evolution of the disease. According to the most recent guidelines, for the patients with systemic sclerosis, also without pulmonary hypertension symptoms, echocardiography screening for the detection of pulmonary hypertension is recommended. Pulmonary arterial hypertension screening programs in systemic sclerosis patients is able to identify milder forms of the disease, allowing earlier management and better long-term outcome.